การบูรณาการด้านออกแบบเชิงกลยุทธ์: กรณีศึกษาธุรกิจของตรา “เอสแอนด์พี”Integration in Strategic Design: A Case Study of “S&P” Brand Business - ฟูสกุล สมพิศ (Asian Creative Architecture, Art and Design, 2018)
Abstract Business required new ideas and strategies all the time or it incurs the risks in sustainable existence.At the same time, design academic faces another threat: lacking on linkage between academic and professional practice outside the classroom. Integrating the design academic with the industrial practice is a good method that solves both problems. This applied research was partially funded by S&P Syndicate Public Company Limited who acted as collaborated partner in this academic integration. The research objectives are as follows: 1) to study the main points of the S&P Syndicate Public Company Limited 2) to identify the design problems and 3) to develop strategies and products for S&P Brand. This research was conducted in 8 steps, with emphasis on studying and analyzing the company’s background; executive’s aims; customers; markets and trends; identifying the design problems; and developing the new strategies and product opportunities for S&P brand. The results included 1) new product strategies that lead to 2) identifying the main design problem resulting from analyzing of three issues: “in what ways could S&P being loved by people in this generation and the next?”; company’s three key business principles: Quality, Value and Virtue; and the key slogan “S&P Simply Delicious”. The main design problem was then divided into five most potential sub-themes, resulting in 3) five design strategies and product outcomes that were demonstrated in the forms of concepts; strategic proposals; and final designs. When the design outcomes were presented to the executives from S&P and the external committees, they were received with favorable responses. In conclusion, this integration of academic and business in strategic design helped developing the students’ skills; opened up an opportunity for S&P to help shaping the more qualified graduates; at the same time S&P could get inspirations that benefitted to its business. This kind of collaboration had both positive aspects and obstacles that needed to be further considered and solved. Keywords: Strategic Design, Integrated Design, New Product Strategies, Design Collaboration, S&P